The Pitfalls of Needs Assessments - Gordon A. Hoke (Journal of Research in Rural Education, 1983)
This report is based on an array of experiences transpiring mainly in the 1970s. Federal legislation of the previous decade introduced much of rural America to categorical programs and their ties to needs assessments. The basic premise of the paper is that collection of valid data is extremely difficult and marked by a complex pattern of flawed assumptions, with socialpolitical issues present at every stage of the needs-goals continuum. A warning is offered that a "rural turnaround" is bringing new residents, often with different expectations and experiences, to regions where their desires for services may clash with priorities already established. Local jurisdictions can thus become vulnerable to demands emerging from unexpected sources.